A belső macedón forradalmi szervezet (VMRO), Magyarország és Olaszország a két világháború között - Hamerli, Petra (Közép-Európai Közlemények, 2015)
In my essay I present the relations of Hungary and Italy with the Internal Macedonian Revolutionary Organization – from the Macedonian name known as „VMRO” – in the Hungarian Horthy era. After the brief presentation of the circumstances of the VMRO’s formation and the causes that made Hungary and Italy to approach to the VMRO, the essay focuses on those acts of the VMRO to which Hungary and Italy paid attention. These were the assassinations made by the VMRO’s members what could have an influence on the political aims of Hungary and Italy. The two States paid attention to the fight between the fractions formed after the murder general Aleksandar Protogerov, a carismatic leader of the VMRO. Both Hungary and Italy were interested in the approachment of the VMRO and the Croatian Revolutionary Party, known as „Ustasha Movement”. The Hungarians and the Italians helped the Macedonian propaganda in the American Continent by the diffusion of the broschures made by the rappresents of the VMRO, and Italy gave them financial support as well to make the propaganda successfull.